Analsisis Dividend Payout Ratio Bank BUMN Indonesia Tahun 2013-2023 - Musadat, Irfan Achmad; Pramayuda, Agung; Ningrum, Retno Widya (Jurnal Accounting Information System (AIMS), 2025)
Following the 1997-1998 crisis, the government implemented banking reforms through the 1998 Banking Law and the establishment of the Indonesia Deposit Insurance Corporation (LPS) to enhance public trust in the financial system. One of the key aspects of banking policy is the dividend policy, as reflected in the Dividend Payout Ratio (DPR). This policy influences investor decisions as well as the financial stability of companies. Dividend stability is considered more attractive than a high DPR, as it indicates a stable company outlook with lower risk. Additionally, dividend policy serves as a signal to creditors regarding a company's ability to meet its financial obligations.This study aims to analyze the relationship between the  Dividend Payout Ratio and the financial performance of banks in Indonesia. The research employs a descriptive quantitative method using secondary data from the financial reports of banks listed on the Indonesia Stock Exchange (IDX). The findings of this study to provide insights into the impact of dividend policy on bank financial performance and its implications for the stability of the financial services sector in Indonesia.